Perioperative immunonutrition intervention on postoperative outcomes among gynecological cancer patients under Enhance Recovery After Surgery setting: a study protocol of explanatory mixed method study - Mat Daud, Zulfitri 'azuan; Mohd Yusof, Barakatun Nisak; Chiouyi, Ho; Abdul Majid, Hazreen (The Public Library of Science (PLoS ), 2024)
Background & Aims: Enhanced Recovery After Surgery (ERAS) has shown significant improvements in postoperative outcomes and a reduction in complications, while immunonutrition (IMN) has been shown to modulate the immune system and inflammatory response. However, many studies have overlooked the crucial aspects of nutrition status and patient perception within the intervention approach. This study aims to investigate the efficacy and explore patients’ acceptance of the IMN intervention in postoperative outcomes among gynecological cancer (GC) patients under the ERAS framework. Methods: This two-phase embedded explanatory sequential mixed-method study design comprises an open-labeled randomized control trial and a qualitative study. The GC participants will be randomly allocated into intervention and control groups. Malaysian adults scheduled for elective surgery will be recruited, with the intervention group receiving IMN for five days before and seven days after elective surgery, while the control group undergoes routine nutritional care before the operation. Both groups will adhere to the ERAS protocol. An exploratory qualitative study will be conducted among GC patients to elucidate their expectations following the trial. Study outcomes include hospitalization duration, change in nutrition status, biochemical profile, functional status, and quality of life. Additionally, the secondary outcome focuses on evaluating the perception of the intervention approach. Quantitative and qualitative data will be analyzed on an intention-to-treat basis and through inductive thematic analysis, respectively. Conclusion: Implementing perioperative IMN intervention within the ERAS framework may contribute to the preservation of better nutrition status and the provision of sufficient dietary intake to support postoperative recovery, and promote better surgical outcomes. Patients' perceptions play a pivotal role in enhancing understanding of disease management and adherence to the intervention approach. Trial registration: NCT06039306.